2022
DOI: 10.1155/2022/5390182
|View full text |Cite|
|
Sign up to set email alerts
|

Application of the Concept of Enhanced Recovery after Surgery in Total Laparoscopic Radical Gastrectomy

Abstract: To explore the clinical effects of total laparoscopic radical gastrectomy under the guidance of the concept of enhanced recovery after surgery (ERAS). Fifty-five patients were perioperatively treated under the concept of ERAS (ERAS group), while the remaining 55 patients were treated under the traditional perioperative concept (control group). The operation time, intraoperative blood loss, the time of first anal exhaust and first postoperative off-bed activity, postoperative length of stay, and incidence of po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%